Farmacovigilancia en paciente adulto mayor con la enfermedad de síndrome de insuficiencia renal crónica - Romero Loaiza, Jorge Luis (Machala : Universidad Técnica de Machala, 2021)
Pharmacovigilance has been considerably important worldwide throughout time to guarantee the safety in the prescription of medicines, the beginning was in 1848 when controversial cases of adverse reactions related to anesthetics occurred, since then until nowadays pharmacovigilance has the purpose of supervising the use of medicines to improve the patient's health. At the end of the XVIII century some syndromes of renal diseases were described, then with the passing of time researchers described more information in the field of nephrology, such investigations executed until today have cooperated efficiently in order to battle with the mortality rate that such disease has procreated. Renal failure represents a high percentage of deaths around the world, since this disease is very frequent in adults with a history of diabetes. The objective of the subsequent study is to analyze and identify the causes of renal failure disease in adult patients, through a severe diagnosis of the factors and consequences associated with CKD, in order to apply pharmacovigilance in the treatment appropriate to the patient's needs. The current document details the symptoms suffered by people suffering from the disease, factors, diagnosis, errors in the dosage and treatment of renal failure. A bibliographic study was carried out based on the research and interpretation of different scientific articles, highlighting the pharmacokinetic factors to start renal treatment. The most common errors attributed to patients suffering from renal failure are smoking, poor diet, diabetes, high blood pressure. It is concluded that it is essential for the biochemist to carry out a pharmacovigilance follow-up of the patient, since he/she must comply with the prescription in order to be able to cope with the disease.
A nivel mundial a lo largo del tiempo la farmacovigilancia ha sido considerablemente importante para garantizar la seguridad en la prescripción de medicamentos, el comienzo fue en el año 1848 cuando pasaron casos controversiales de reacciones adversas relacionadas con anestésicos, desde ese entonces hasta la actualidad la farmacovigilancia tiene la finalidad de supervisar el empleo de medicamentos para mejorar la salud del paciente. En los finales del siglo XVIII se describieron algunos síndromes de enfermedades renales, después con el pasar del tiempo los investigadores describieron más información en el campo de nefrología, dichas investigaciones ejecutadas hasta la actualidad han cooperado de forma eficiente para así poder batallar con la tasa de mortalidad que dicha enfermedad ha procreado. La insuficiencia renal representa un elevado porcentaje de muertes alrededor del mundo, ya que esta enfermedad es muy frecuente en las personas adultas que tienen antecedentes de diabetes. El objetivo del posterior estudio es analizar e identificar las causas de la enfermedad de insuficiencia renal en los pacientes adultos, a través de un diagnóstico severo de los factores y consecuencias asociadas a IRC, para poder aplicar la farmacovigilancia en el tratamiento adecuado a las necesidades del paciente. El actual documento detalla los síntomas que sufren las personas que padecen la enfermedad, factores, diagnóstico, errores en la posología y tratamiento de insuficiencia renal. Se efectuó un estudio bibliográfico fundamentado en la investigación e interpretación de distintos artículos científicos, destacando los factores farmacocinéticos para empezar el tratamiento renal.
Keywords: IRC; MORTALIDAD; FARMACOVIGILANCIA; DIAGNOSTICO